2022
DOI: 10.5125/jkaoms.2022.48.5.259
|View full text |Cite
|
Sign up to set email alerts
|

Associations between obstructive sleep apnea and painful temporomandibular disorder: a systematic review

Abstract: The relationship between obstructive sleep apnea (OSA) and diverse types of pain conditions have been proposed. However, no consensus on the relationship between OSA and painful temporomandibular disorders (TMDs) has been established. Therefore, this systematic review has been conducted to review the existing literatures and provide comprehensive synthesis of such literatures about OSA and painful TMDs using the evidence-based methodology. A literature search was conducted using two electronic databases, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Similarly, our UVMR findings revealed no causal links of genetically determined education with autoimmune traits including SLE and Sjogren's syndrome, despite adults with immune‐mediated rheumatic diseases showing a significant relevance to TMDs. The disparities between MR and observational studies may, in part, be attributed to genetic variance in the former and potential bias from residual confounding or reverse causation in the latter 23 . Furthermore, certain lifestyles and socioeconomic factors, such as initial smoking, smoking history and average household income, were excluded from our mediation analyses due to their significant bidirectional causal associations with education, part of which are in line with a recent MR study between education and socioeconomic status 12,14 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Similarly, our UVMR findings revealed no causal links of genetically determined education with autoimmune traits including SLE and Sjogren's syndrome, despite adults with immune‐mediated rheumatic diseases showing a significant relevance to TMDs. The disparities between MR and observational studies may, in part, be attributed to genetic variance in the former and potential bias from residual confounding or reverse causation in the latter 23 . Furthermore, certain lifestyles and socioeconomic factors, such as initial smoking, smoking history and average household income, were excluded from our mediation analyses due to their significant bidirectional causal associations with education, part of which are in line with a recent MR study between education and socioeconomic status 12,14 .…”
Section: Discussionmentioning
confidence: 85%
“…The disparities between MR and observational studies may, in part, be attributed to genetic variance in the former and potential bias from residual confounding or reverse causation in the latter. 23 Furthermore, certain lifestyles and socioeconomic factors, such as initial smoking, smoking history and average household income, were excluded from our mediation analyses due to their significant bidirectional causal associations with education, part of which are in line with a recent MR study between education and socioeconomic status. 12,14 As a potential risk factor for TMDs, underweight was not identified as the mediator in our study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, about the 51% of OSA patients showed signs and symptoms of TMD and about 30% of TMD patients met the diagnostic criteria for insomnia and OSA 29,30 . The linkage among these conditions may be found in the hyperalgesia that OSA patients might experience, in relation to the fragmented sleep and hypoxemia that might enhance peripheral and central pain sensitization, thus increasing spontaneous pain 29,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, about the 51% of OSA patients showed signs and symptoms of TMD and about 30% of TMD patients met the diagnostic criteria for insomnia and OSA. 29,30 The linkage among these conditions may be found in the hyperalgesia that OSA patients might experience, in relation to the fragmented sleep and hypoxemia that might enhance peripheral and central pain sensitization, thus increasing spontaneous pain. 29,31,32 However, a recent crosssectional study performed by Bartolucci et al 33 showed that the prevalence of TMDs in adults with OSA was not significantly higher compared to healthy controls in their cohort; therefore, further studies should confirm this potential correlation providing reliable evidence on the role of conservative treatments for TMD in patients affected by OSA.…”
Section: Ta B L Ementioning
confidence: 99%